Electrochemical immunosensor based on MOF for rapid detection of 6-benzyladenine in bean sprouts - Liu, Qingqing; Xing, Yunrui; Pang, Xinghao; Zhan, Ke; Sun, Yaning; Wang, Na; Hu, Xiaofei (Journal of food composition and analysis, 2023)
6-benzylaminopurine (6-BA) is a widely used plant growth promoter. However, it can lead to precocious puberty and cause acute poisoning and even cancer of consumer. Thus, it is necessary to establish rapid and sensitive method for the detection of 6-BA. Electrochemical immunosensor is a new kind of biosensor, which combines the high selectivity of antibody with the high sensitivity of electrochemical sensor. In this study, an electrochemical immunosensor was developed for the detection of 6-BA in bean sprouts. The carbon material of Zn/Ni-ZIF-8–800 derived from bimetal-organic framework was synthesized by solvothermal method. Then, Zn/Ni-ZIF-8–800 was ultrasonically mixed with the highly conductive graphene, and the gold nanoparticles (AuNPs) were reduced by constant potential deposition (AuNPs/Zn/Ni-ZIF-8–800 @graphene). Finally, the antibody of 6-BA was combined with the prepared material to make an electrochemical immunosensor. The prepared materials were characterized by XRD, FTIR, SEM, TEM and XPS analyses. In addition, the electron transfer abilities of the modified sensors were investigated by CV and EIS. The established immunosensor presented a wide linear range (0.08–50 ng/mL), low detection limitation (0.24 ng/mL) and satisfactory recovery rates towards 6-BA (90.9–105.0 %). In brief, an electrochemical immunosensor with high sensitivity and selectivity was developed, which could be used to detect 6-BA in bean sprouts effectively. •An electrochemical sensor based on AuNPs/Zn/Ni-ZIF-8–800 @graphene for the detection of 6-BA in bean sprouts has not been reported yet.•The detection limit of 6-BA in bean sprouts is 0.24 ng/mL, which is lower than other sensors.•The prepared sensor has high selectivity and long-term stability, which lays a foundation for the simple, rapid and sensitive detection of 6-BA in bean sprouts.